2017
DOI: 10.1002/mc.22661
|View full text |Cite
|
Sign up to set email alerts
|

Ski regulates Smads and TAZ signaling to suppress lung cancer progression

Abstract: Ski, the transforming protein of the avian Sloan-Kettering retrovirus, displays both pro- and anti-oncogenic activities in human cancer. The mechanisms underlying these conflicting observations have not been fully understood. Herein, we investigated the mechanism underlying the tumor suppressor activity of Ski. To investigate the effect of Ski re-activation on TGF-β and Hippo/TAZ pathway, we measured its effect on the endogenous Smad target genes (PAI-1 and P15 ) and TAZ target gene CTGF. The results revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 46 publications
2
14
0
Order By: Relevance
“… 97 100 Recently, it has been reported that the Ski gene is hypermethylated and silenced in human primary lung cancer tissues, supporting Ski function as a tumor suppressor. 101 Ski mRNA levels are also modulated by different miRNAs, such as miR-21, miR-29a, miR-155, and miR-127-3p (Fig. 2 ).…”
Section: Ski and Snon Are Major Negative Regulators Of The Tgf-β Signmentioning
confidence: 99%
See 2 more Smart Citations
“… 97 100 Recently, it has been reported that the Ski gene is hypermethylated and silenced in human primary lung cancer tissues, supporting Ski function as a tumor suppressor. 101 Ski mRNA levels are also modulated by different miRNAs, such as miR-21, miR-29a, miR-155, and miR-127-3p (Fig. 2 ).…”
Section: Ski and Snon Are Major Negative Regulators Of The Tgf-β Signmentioning
confidence: 99%
“…The Ski protein interacts with Lats2 and enhances its activity to destabilize the TAZ protein in mammary epithelial cells, 69 whereas, in lung cancer, the Ski gene is silenced by methylation and, consequently, Ski is unable to inhibit TAZ. 101 Ski and SnoN negatively regulate the expression of the Indian hedgehog ( Ihh ) gene in primary chondrocytes via different transcriptional complexes: SnoN/Smad2 and HDAC4 form a complex with high affinity; whereas, the Ski/Smad3 complex has a lower affinity. 210 Furthermore, gefitinib is a drug that is used to treat lung cancer; thus, the IL-6 cytokine induces Stat3 phosphorylation to repress Smad3 expression, promoting gefitinib resistance, and Stat3 interacts with Ski and SnoN to inhibit the R-Smad/co-Smad complex.…”
Section: Regulation Of Tgf-β/smad Signaling By Ski and Snonmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study found that Ski inhibits YAP and mainly TAZ in lung because it induces their phosphorylation mediated by LATS1/2, thus inducing their proteasome-mediated degradation but not their cytoplasmic translocation. In 56% of NSCLC tissues, the Ski promoter is hypermethylated and its downregulation is associated with poorer prognosis [ 130 ].…”
Section: Hippo Pathway In Lung Cancermentioning
confidence: 99%
“…We carried out BioID2 analyses to address novel mechanisms by which SKI interacts, and potentially regulates, Hippo signaling in primary cardiac fibroblasts. Previous oncological studies suggest that SKI interacts with several core Hippo pathway components, including LATS2; however, they utilized cancer cell lines (i.e., breast, kidney, and lung) [40,58]. They revealed a decrease in TAZ protein expression with ectopic SKI expression, as well as a marked reduction in cell proliferation, migration, and tumorigenicity.…”
Section: Discussionmentioning
confidence: 97%